Al-Tafsîr Al-Kabîr: Penafsiran Maudhu’i Ibnu Taymiyyah Dalam Balutan Tahliliy - Muhamad Rezi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Not many people know the book Tafsir al-Kabîyr as people know the author Ibn Taymiyyah and his other works. It could be seeming from the lack of this book as a reference in the study of Qur’an and Tafsir. In fact, it was Ibn Taymiyyah who initiated the Tafsir bil-ma'tsur method used by his student Ibn Kathir. But Tafsir al-Kabîr is in fact not as complete and well-known as Ibn Kathir's Tafsir. This could be due to the incomplete verses that are interpreted in the book. This article aims to describe the book Tafsir al-Kabîr Ibn Taymiyyah and explore Ibn Taymiyyah's style of discussion in Tafsir al-Kabîr by describing several examples. This type of research is literature research with analytical content analysis and descriptive-analytical approaches. In his Tafsir, Ibn Taymiyyah interpreted them thematically but then collected the explanations in the order of the manuscripts which impressed Tahliliy. Substantively, Ibn Taymiyyah's interpretation in Tafsir al-Kabîr is not as detailed as he did as he formulated the Muqaddimat fi Ushul al-Tafsir book. Ibn Taymiyyah, only relates the diction of the verse which is his focus and is discussed linguistically. Ibnu Taymiyyah also quoted several related Hadiths. However, the discussion of ideas and ideology that Ibn Taymiyyah usually does is not seen in his many explanations in his other works.